2018
DOI: 10.1016/j.cyto.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in TLRs influence circulating cytokines production in Plasmodium vivax malaria

Abstract: The efficiency of the immune system has been shaped throughout the evolutionary process allowing adaptations. In a Plasmodium vivax infection, the host attempts to develop an innate immune response to keep in check the parasite that is associated with inflammatory and regulatory processes. Production of pro-inflammatory and regulatory cytokines simultaneously appears to be a balancing mechanism for the host to prevent the onset of severe disease. Changes in the dynamics of circulating cytokines production can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Cytokine‐induced inhibition of the expression and activity of CYP enzymes in hepatocytes is one likely mechanism. The host immune response against P. vivax triggers production and increased circulating levels of several proinflammatory and regulatory cytokines, which influence the pathogenesis and severity of the disease, and recurrence of acute episodes 11–15 Our results verified the increase in circulating IL‐6, IL‐8 and IL‐10 in acute vivax malaria (phase 1), and reversal to baseline (IL‐6 and IL‐10) or considerable reduction (IL‐8) at the end of the 7‐day combined chloroquine‐primaquine treatment (phase 2), in agreement with previous results 11 . The time course of changes in circulating IL‐6 and IL‐10, and to a lesser degree IL‐8, parallels the transient inhibition of CYP2C19 activity observed in phase 1 of this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cytokine‐induced inhibition of the expression and activity of CYP enzymes in hepatocytes is one likely mechanism. The host immune response against P. vivax triggers production and increased circulating levels of several proinflammatory and regulatory cytokines, which influence the pathogenesis and severity of the disease, and recurrence of acute episodes 11–15 Our results verified the increase in circulating IL‐6, IL‐8 and IL‐10 in acute vivax malaria (phase 1), and reversal to baseline (IL‐6 and IL‐10) or considerable reduction (IL‐8) at the end of the 7‐day combined chloroquine‐primaquine treatment (phase 2), in agreement with previous results 11 . The time course of changes in circulating IL‐6 and IL‐10, and to a lesser degree IL‐8, parallels the transient inhibition of CYP2C19 activity observed in phase 1 of this study.…”
Section: Discussionsupporting
confidence: 90%
“…[5][6][7][8] Increased levels of circulating proinflammatory cytokines are hallmarks of human parasitic diseases such as leishmaniasis 9,10 and malaria. [11][12][13][14][15] We have previously shown that the phenotypic activities of CYP3A4 and CYP2C19 were significantly reduced during acute visceral leishmaniasis and restored after curative chemotherapy; suppression of CYP activity was attributed to increased plasma concentrations of proinflammatory cytokines during active disease. 16 Regarding human malaria, there is only limited information for Plasmodium falciparum, suggestive of reduced activity of CYP1A2 and CYP3A enzymes.…”
mentioning
confidence: 99%
“…The positive and negative correlations are considered significant when p < 0.05. The correlation index (r) was used to categorize the correlation strength as being weak ( r ≤ 0.35), moderate ( r ≥ 0.36 to r ≤ 0.67), or strong ( r ≥ 0.68), as previously described (30, 31). The levels of statistical significance defined in both cases were p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…The AA genotype proved to be protective against the development of this parasite in a local population of Pakistan [77]. Additionally, TLR4 A299G, TLR6 S249, and TLR 9-1486C/T influence the levels of circulating cytokines IL-6, IFN-γ, IL-12, IL-10, and IL-4 during a P. vivax infection [78].…”
Section: Other Protozoansmentioning
confidence: 99%